ANALISIS FRAMING PEMBERITAAN TERHADAP âSERINGNYA KECELAKAAN BERKENDARA DI WAKTU SENJAâ PADA TABLOID MOTORPLUS - Rizky, Fuad (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
The increasing number of two-wheelers in the capital Jakarta from year to year, causing the capitalâs streets eachday in both the morning rush hour when people like to start their daily activities and at the time at dusk or in theevening before the public knew back home after activity packed by a two-wheeled vehicle or motorcycle. The riskof accident was definitely always there in times like these where the riders start to feel tired. The good conditionof the eyes or other body parts, in this case highlights the tabloid MotorPlus more about eye conditions can causeaccidents, because the eyes need full concentration while driving, the concentration of reduced eye sensitivityberkuarang concentration also other limbs, because it took the eyes of dark adaptation and light and vice versa.In this study the authors wanted to see how tabloid MotorPlus framing the reality of frequent accidents when drivingat dusk, especially in Jakarta. This research is based by the constructionist paradigm that highlight aspects ofreality by the media. So the researchers used a qualitative research is the description that only describe a situationor event, make a picture and framing analysis by Robert N entman.Results of this study found that framing MotorPlus tabloid news of the frequent accidents when driving at dusk asseen small but big impact and should be known by bikers, that the eye may also be the cause of the accident in additionto the lack of knowledge to drive properly and correctly, ( lack of driving skills in driving individual skills),as well as physical strength and stamina after seharrian activity, due to the motor driving all members onggotabody moves, and all require concentration.Seen from tabloid news motorplus just looking for the appropriate resource persons in such bidanngnya Ditlantas,NGOs, ministries of transportation. Although community and non-governmental organizations have socialized ondriving safety to the community and the individual rider. Did not rule out the community members and individualriders infallible.